Método de Faddeev-Jackiw na mecânica clássica - Caro, L. G. [UNESP]; Pimentel, B. M. [UNESP]; Zambrano, G. E. R. (Sociedade Brasileira de Física, 2021)
Constrained theories are of great interest in theoretical physics, since all known theories of fundamental interactions present gauge freedom, which is a type of singular feature of the theory and implies that the theory is constrained. On the other hand, since the quantum theory is commonly constructed on a Hamiltonian structure, the canonical quantization process is the most suitable if the Hamiltonian formulation of the classical theory is available. Thus, the necessity to obtain the Poisson Brackets (PB) of the canonical variables in the theory to be quantized arises. In the present work we study the Faddeev and Jackiw proposal, reviewed by Barcelos-Neto and Wotzasek, to obtain the PB in singular theories by means of an approach employing the geometric elements of the Hamiltonian theory themselves. The process was built specifically for matter point mechanics and subsequently was implemented in a sequence of examples, obtaining the fundamental PB in each of them, thus preparing the ground for quantization.

As teorias de vínculos são de grande interesse na física teórica, pois todas as teorias conhecidas das interações fundamentais apresentam liberdade de calibre, que é um tipo de caráter singular da teoria, o que implica que ela possui vínculos. Por outro lado, uma vez que a teoria quântica é comumente construída sobre uma estrutura hamiltoniana, o processo de quantização canônica é o mais apropriado se se dispuser da formulação hamiltoniana da teoria clássica. Assim, surge a necessidade de se obter os parênteses de Poisson (PP) das variáveis canônicas na teoria clássica a ser quantizada. O presente trabalho estuda a proposta de Faddeev e Jackiw, revisada por Barcelos-Neto e Wotzasek, para obter os PP em teorias singulares por meio de uma abordagem que faz uso dos elementos geométricos próprios da teoria hamiltoniana. O processo foi construído especificamente na mecânica dos pontos materiais e posteriormente foi implementado em uma série de exemplos, obtendo os PP fundamentais em cada um deles e deixando assim o terreno pronto para a quantização.
Faddeev-Jackiw method in classical mechanics
Keywords: Classical mechanics; symplectic form; constrained systems; Mecânica clássica; forma simplética; sistemas singulares